2009
DOI: 10.1177/1753425908099317
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide inhibits lipopolysaccharide-induced tumor necrosis factor-α production via down-regulation of MyD88 expression

Abstract: The effect of thalidomide on lipopolysaccharide (LPS)-induced tumor necrosis factor (TNF)-a production was studied by using RAW 264.7 murine macrophage-like cells. Thalidomide significantly inhibited LPS-induced TNF-a production. Thalidomide prevented the activation of nuclear factor (NF)-kB by down-regulating phosphorylation of inhibitory kB factor (IkB), and IkB kinase (IKK)-a and IKK-b Moreover, thalidomide inhibited LPS-induced phosphorylation of AKT, p38 and stress-activated protein kinase (SAPK)/JNK. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 33 publications
4
34
1
4
Order By: Relevance
“…These results show deleterious effect of thalidomide on proinflammatory cytokine production and accentuation of IL-10 production. Recently, Noman et al have shown that thalidomide inhibits TNF-α production from RAW 264.7 murine macrophages-like cells, when they are stimulated with lipopolysaccharide (LPS) by inhibiting the NF-κB pathway [33]. They found that thalidomide treatment decreased the expression of myeloid differentiation factor 88 (MyD88) protein and mRNA in the macrophages, involved in NF-κB mediated down signaling leading to exaggerated inflammatory immune response in response to infectious or inflammatory agent.…”
Section: Discussionmentioning
confidence: 96%
“…These results show deleterious effect of thalidomide on proinflammatory cytokine production and accentuation of IL-10 production. Recently, Noman et al have shown that thalidomide inhibits TNF-α production from RAW 264.7 murine macrophages-like cells, when they are stimulated with lipopolysaccharide (LPS) by inhibiting the NF-κB pathway [33]. They found that thalidomide treatment decreased the expression of myeloid differentiation factor 88 (MyD88) protein and mRNA in the macrophages, involved in NF-κB mediated down signaling leading to exaggerated inflammatory immune response in response to infectious or inflammatory agent.…”
Section: Discussionmentioning
confidence: 96%
“…The suppression activity of all ZM compounds against LPS-induced TNF-α production is mainly attributed to the isoindoline1,3-dione moiety in the ZM compounds. It has been shown that phthalimide (isoindoline1,3-dione) and thalidomide analogues do inhibit synthesis of TNF-α from LPS-activated macrophages through impairing the intracellular LPS signaling such as NF-kB activation, MyD88 expression and p38 phosphorylation [28][29][30][31]. Furthermore, since oral administration 20 mg/kg of ZM compounds showed antiinflammatory in carrageenan-induced rat paw edema within hours post administration [9] and modulated LPS-induced cytokine in mice spleen, these ZM compounds are readily bioavailable in blood and suggest proper pharmacokinetic properties for anti-inflammatory drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the MyD88-dependent pathway involves the sequential recruitment of the adaptor molecule MyD88, IRAK family proteins and TRAF6 (38,39). TRAF6 subsequently triggers the activation of MAP kinases and, as a result of TAK-1-mediated IKK activation, NF-κB (40).…”
Section: Discussionmentioning
confidence: 99%